2004
DOI: 10.1194/jlr.m400064-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ω-Hydroxylation of phytanic acid in rat liver microsomes

Abstract: The 3-methyl-branched fatty acid phytanic acid is degraded by the peroxisomal ␣ -oxidation route because the 3-methyl group blocks ␤ -oxidation. In adult Refsum disease (ARD), peroxisomal ␣ -oxidation is defective, which is caused by mutations in the gene coding for phytanoyl-CoA hydroxylase in the majority of ARD patients. As a consequence, phytanic acid accumulates in tissues and body fluids. This study focuses on an alternative route of phytanic acid degradation, -oxidation. The first step in -oxidation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…1A. The spectrum depicts a prominent loss of H 35 Cl from the [M Ϫ H] Ϫ ion. A similar facile loss of HCl has been described previously for 2-ClHA (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A. The spectrum depicts a prominent loss of H 35 Cl from the [M Ϫ H] Ϫ ion. A similar facile loss of HCl has been described previously for 2-ClHA (23).…”
Section: Resultsmentioning
confidence: 99%
“…2-ClAdA gradient 2 was performed at 300 l/min as follows: 0 -4 min 100% A to 90% A, 4 -12 min 90% A to 20% A, 12-18 min 20% A to 0% A, 18 -23 min 0% A, 23-24 min 0% A to 100% A, and 24 -35 min 100% A for re-equilibration. For both elution gradients, the transitions from m/z 179 3 143 for 2- 35 ClAdA and m/z 181 3 143 for 2- 37 ClAdA were monitored in the negative ion mode. For stable isotope-labeled 2-ClAdA, the following SRMs were used: m/z 181 3 145 for 2- For some analyses, as indicated, ESI-MS/MS was also performed on analytes in methanol.…”
Section: Esi-ms/ms and Lc-ms/ms-formentioning
confidence: 99%
“…GC-MS Analysis-GC-MS was performed according to a published method (30) with modifications on an Agilent GC6890 gas chromatographer coupled to a JMS-AM150 mass spectrometer (Jeol, Tokyo, Japan). A 30-m HP-5 column (0.32-mm inner diameter with 0.25-m filter, Agilent) was used with helium as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…2C), although the peak is small in comparison with that of the -OH-PA (retention time ϭ 22.4 min, m/z ϭ 457, with a characteristic fragment of m/z ϭ 103, Fig. 2D) (Komen et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Further oxidation of the terminal hydroxyl group to the acid, a reaction catalyzed by both the CYP4 enzymes and alcohol/aldehyde dehydrogenases (Sanders et al, 2005), produces dicarboxylic acids that can undergo ␤-oxidation from either end. It has been reported that phytanic acid can also be -hydroxylated, giving rise to an -hydroxy alcohol that, after oxidation to the acid, can be degraded normally by ␤-oxidation (Komen et al, 2004(Komen et al, , 2005. Studies of phytanic acid -hydroxylation have so far only been carried out with microsomal systems that do not allow identification of the actual enzymes involved in the reaction (Komen et al, 2004(Komen et al, , 2005.…”
mentioning
confidence: 99%